Diplomatinio protokolo kaitai įtaką darantys veiksniai: komunikacinis aspektas - Grebliauskienė, Beata; Sueldo, Mariana (Information & Media, 2008)
Straipsnyje analizuojamas diplomatinis protokolas ir jo kaita komunikaciniu aspektu. Traktuojant protokolą kaip komunikacijos sklandumo ir efektyvumo užtikrinimo priemonę, tiriamos specifinių protokolo bruožų atsiradimo aplinkybės bei priežastys, atskleidžiami diplomatinio protokolo klostymuisi bei raidai įtaką darę veiksniai. Diplomatinis protokolas kaip komunikacijos proceso dalis analizuojamas keliais aspektais: komunikacijos proceso dalyvių tikslai, proceso dalyvių komunikaciniai gebėjimai ir vis daugėjimas šių dalyvių bei komunikacijos intensyvėjimas. Aptariami diplomatinės komunikacijos besikeičiantys tikslai pereinant nuo neapibrėžtumo vengimo iki siekio įtikinti. Atkreipiamas dėmesys į protokolui būdingą, tačiau nesavitikslį neverbalikos formų vartojimą, ritualų ir ceremonijų gausą nuo viduramžių iki mūsų dienų. Pagrindiniai žodžiai: diplomatinis protokolas, komunikacijos procesas, diplomatinio protokolo kaita, veiksniai. The influence factors in the development of diplomatic protokol: communicative perspective Mariana Sueldo, Beata Grebliauskienė Summary This paper provides an analysis of diplomatic protocol as part of the communication process, more specifically as a code of communication and the factors which have mostly influenced its development. Protocol being understood as a means to ensure effective and clear communication, the circumstances and reasons for the emergence of protocol are discussed. Three main aspects of protocol as a communication code are here considered as the most significant, namely: the participants in the diplomatic communication process and their aims, the communication abilities of individuals taking part in such situations, and the gradually and historically changing number of the participants involved in the diplomatic communication process, as well as the intensity of communication. This article unveils these three factors within the area of communication, focusing respectively on each of them, starting with an overview of ritualized and rule-base interpersonal communication as a means to reduce uncertainty. Then diplomatic communication as a persuasive tool is analysed as a ruled self-expression within a purposefully created context, where the participants seek individual goals. Then follows a brief analysis of the changing communication goals, ranging from the avoidance of uncertainty to the seek of persuassion. Attention is drawn to the frequent use of non-verbal communication forms, rituals and ceremonies as an integral component of protocol, from its emergence in the Middle Ages till our times. span>